Risk factors for elderly acute decompensated heart failure patients with diabetic nephropathy: a retrospective study - Li, Xiaodong; Li, Xinyue; Li , Baoxin; Wang, Xiangdong (Journal of the Pakistan Medical Association, 2022)
Risk factors that contribute to the development of heart failure include chronic kidney disease and diabetes. Elderly patients with diabetic nephropathy are more likely to develop heart failure. We analysed laboratory data and clinical characteristics of elderly patients with diabetic nephropathy to explore the risk factors for therapeutic effect of acute decompensated heart failure (ADHF). One hundred and five elderly patients with diabetic nephropathy, admitted in the Nephrology Ward of Baoding No1 Central Hospital Baoding, China, between June 2018 and June 2020, were enrolled in this study. They were classified as biochemically unaltered group (21 cases) and biochemically recovering group (84 cases). The clinical data, laboratory examination, therapy, and outcome of the participants were collected for analysis retrospectively. Low-density lipoprotein (LDL), C-reactive protein (CRP) and 24-hour urine protein are independent risk factors for the therapeutic efficacy of ADHF in elderly patients with diabetic nephropathy. Keywords: Diabetic Nephropathy, Chronic kidney disease, Risk factors, Biomarkers.